Spontaneous passage of common bile duct stones: predictive factors and impact on post-ERCP complications - Wasuwit Wanchaitanawong; Phichayut Phinyo; Thanaput Kunlayawutipong; Nawapol Chatkul; Phuripong Kijdamrongthum; Nithi Thinrungroj (PLoS ONE, 2026)
Background Spontaneous passage of common bile duct stones (CBDSs) may render endoscopic retrograde cholangiopancreatography (ERCP) unnecessary. Although predictors of passage have been described, most prior studies were limited by a small number of events, and the impact of spontaneous passage on post-ERCP complications remains under-investigated. This study aimed to identify clinical predictors of spontaneous passage and evaluate its association with post-ERCP complications. Methods We conducted a retrospective cohort study of patients diagnosed with CBDSs who underwent endoscopic ultrasonography (EUS) or ERCP at a tertiary referral center. Spontaneous passage was defined as the absence of stones confirmed during the procedure. Multivariable risk regression was used to identify predictors of passage and to assess the association between spontaneous passage and post-ERCP complications. Results Spontaneous passage was observed in 113 of 404 patients (28%). Independent predictors of spontaneous passage included younger age (RR 0.88 per 10 years; 95% CI 0.81–0.96), smaller CBDS size (RR 0.78 per 1 mm; 95% CI 0.71–0.85), and single CBDS (RR 1.64; 95% CI 1.04–2.61). Regarding complications, post-ERCP pancreatitis (PEP) occurred more frequently in patients with spontaneous passage compared to those without (16.5% vs 7.6%, P = 0.01). After adjusting for relevant confounders, including procedural factors, spontaneous passage remained an independent risk factor for PEP (RR 2.48, 95% CI 1.25–4.92). Conclusions Spontaneous passage of CBDSs is an independent risk factor for PEP. Younger age, smaller stone size, and a single stone are significant predictors of passage. These findings suggest that pre-procedural risk stratification and non-invasive confirmation of ductal clearance may be beneficial in selecting appropriate candidates, potentially reducing unnecessary ERCP and associated complications.